The Cytotoxic Activities of n-Hexane Extract of Pumpkin Seed (Cucurbita moschata) on WiDr Colon Cancer Cell and HeLa Cervical Cancer Cell - Krisridwany, Annisa; Winy Cintya Ningrum, Dhecella; Susilowati, Fitria; Octavia, Rima; Winanta, Aji (Asian Journal of Pharmaceutical Research and Development, 2023)
Colon cancer and cervical cancer are types of cancer with a high prevalence, contributing 10% and 3.1% respectively of the total new cancer cases. Nutrition and dietary factors play an important role in human carcinogenesis. Natural plants contain substances that can be beneficial to human health. One such plant is the pumpkin (Cucurbita moschata). Pumpkin seeds are thought to have many biological activities for health, such as antioxidant, anticancer, and anti-inflammatory effects. This study aimed to determine the cytotoxic activity of n-hexane extract of pumpkin seed against colon (WiDr) and cervical (HeLa) cancer cells using the MTT Assay method. The method used in this study consisted of the preparation of plant extracts, phytochemical screening, total content of metabolites. The results proved that the n-hexane extract of pumpkin seed was observed containing flavonoids, alkaloids, and steroids. The content of highest total content, namely flavonoid compounds as much as 616.46 mg/L. The n-hexane extract of pumpkin seed showed cytotoxic activity for WiDr cells and HeLa cells with an IC50 value of 193.44 µg/mL and 237.702 µg/mL, respectively. The results of this study can be concluded that n-hexane extract of pumpkin seed can be used as a chemopreventive agent, due to the moderate cytotoxic test results.